Short- and long-term changes of the pharyngeal airway after surgical mandibular advancement in Class II patients: a three-dimensional retrospective study - Ristow, Oliver; Rückschloß, Thomas; Berger, Moritz; Kargus, Steffen; Krisam, Johannes; Seeberger, Robin; Engel, Michael; Hoffmann, Jürgen; Freudlsperger, Christian (Journal of cranio-maxillofacial surgery, 2018)
Purpose To evaluate the short- and long-term impact of mandibular-only advancement on pharyngeal airway space (PAS) changes by using cone-beam computed tomography (CBCT) and a new segmentation software. Furthermore, to determine whether a correlation exists between forward movement and PAS gain. Materials and methods A retrospective evaluation of a homogeneous cohort of Class II patients who had undergone mandibular-only advancement was performed. Pre- (T0), post- (T1), and 1-year post-operative (T2) CBCT scans were obtained in each case, and the changes in PAS parameters (volume and smallest cross-sectional area) were compared with new segmentation software. Mandibular advancement was measured and correlated with PAS parameters. Results A significant postoperative gain in all airway parameters compared with baseline was shown for T1 (p = 0.02), with an additional increase for T2 (p < 0.001). No significant linear association between the movement of the measurement points and any other PAS parameters could be discerned (p > 0.05). Conclusion Our findings indicate that bilateral mandibular-only advancement surgery results in a significant widening of the PAS in Class II patients. Long-term adaption of the PAS also occurs after surgery implying an additional gain of PAS over time. Sicat Air® software seems to be a sufficient and promising tool for PAS evaluation.
Available online 6 November 2017
Gesehen am 28.06.2018